Monocytes and T cells incorporated in full skin equivalents to study innate or adaptive immune reactions after burn injury - Mulder, Patrick P.G.; Vlig, Marcel; Elgersma, Anouk; Rozemeijer, Lotte; Mastenbroek, Leonore S.; Middelkoop, Esther; Joosten, Irma; Koenen, Hans J.P.M.; Boekema, Bouke K.H.L. (Frontiers in Immunology, 2023)
Introduction Thermal injury often leads to prolonged and excessive inflammation, which hinders the recovery of patients. There is a notable absence of suitable animal-free models for investigating the inflammatory processes following burn injuries, thereby impeding the development of more effective therapies to improve burn wound healing in patients. Methods In this study, we established a human full skin equivalent (FSE) burn wound model and incorporated human peripheral blood-derived monocytes and T cells. Results Upon infiltration into the FSEs, the monocytes differentiated into macrophages within a span of 7 days. Burn-injured FSEs exhibited macrophages with increased expression of HLA-DR+ and elevated production of IL-8 (CXCL8), in comparison to uninjured FSEs. Among the T cells that actively migrated into the FSEs, the majority were CD4+ and CD25+. These T cells demonstrated augmented expression of markers associated with regulatory T cell, Th1, or Th17 activity, which coincided with significant heightened cytokine production, including IFN-γ, IL-4, IL-6, IL-8, IL-10, IL-12p70, IL-17A, IP-10 (CXCL10), and TGF-β1. Burn injury did not impact the studied effector T cell subsets or cytokine levels. Discussion Collectively, this study represents a significant advancement in the development of an immunocompetent human skin model, specifically tailored for investigating burn-induced innate or adaptive immune reactions at the site of burn injury.